IMPLEMENTASI KEBIJAKAN PENANGANAN PANDEMI COVID-19 DI KOTA CIMAHI PROVINSI JAWA BARAT - Bertha Lubis (Jurnal Media Birokrasi, 2021)
The purpose of the research conducted in Cimahi City, related to the Implementation of the Covid-19 Pandemic Handling Policy, was because Cimahi City, including the areas affected by the Covid-19 transmission in West Java province. So that researchers want to know and look for and get data on the extent of the policies for handling Covid-19 in the City of Cimahi carried out by the ranks of the Cimahi City government apparatus. The method used in this study is a descriptive qualitative method with an inductive approach. Sources of data obtained from print media and electronic media as well as documentation. The results obtained are that the implementation of policies carried out in handling Covid-19 in Cimahi City, is where the Cimahi City Government to support the implementation of handling the Covid-19 pandemic, has carried out refocusing and relocating the Cimahi City APBD budget, this is done to support the acceleration of handling Covid-19 and anticipate transmission. Covid-19 which is increasingly widespread in Cimahi City. The conclusion obtained, with this policy, the Cimahi City Government has temporarily been able to control the acceleration of the transmission of Covid19. And to anticipate in the future if Covid-19 does not slow down in 2021, the Cimahi City Government allocates a larger APBD for handling Covid-19, and increasing the economic growth of the City of Cimahi. Keywords: Policy implementation, Covid-19 pandemic